Perception of drought by farmers and its impact on farming and irrigation practices - Masmoudi M.M.; Nagaz K.; Ben Mechlia N. (Economics of drought and drought preparedness in a climate change context, 2010)
Climate change scenarios predict negative impacts on agriculture in the southern Mediterranean regions. Preparedness for increasingly frequent droughts requires a good knowledge on how chronic water shortages may affect production and cropping systems. This work investigates recent variations in agricultural production and in cropping practices in Tunisia as induced by a rapidly changing environment. Using production statistics and climatic records over the period 1984-2005, our analysis shows that variation of the agricultural production could be explained by the Standardized Precipitation Index (R² = 0.45), and that resilience to drought could be evaluated in the same manner. Data from surveys was used to identify adjustments adopted by farmers under the pressure of water scarcity in semi arid (Nabeul) and arid (Medenine) environments. Contrasting changes in cropping systems seem to be taking place for both regions. Contrast is also observed between irrigation strategies adopted by farmers. In Nabeul, large citrus growers having access to water from canal tend to over irrigate whenever water is available in order to minimize risks of water delivery failure from public networks. In contrast small farmers using shallow wells in Medenine seek practices such as deficit irrigation and intercropping in order to optimize water use. It is our view that options to face drought under increasing environmental stress should have a dynamic nature integrating adaptive practices used by farmers.
2. International Conference on Drought Management, 2010/03/04-06, Istanbul (Turkey)